An Analysis of Students’ Anxiety in Learning English - Opriorika, Genda -; Mulyadi, Mulyadi -; Sufiyandi, Sufiyandi - (Journal of English Education and Teaching, 2023)
This research aimed to determine the level and the factors that caused students’ anxiety in learning English that is faced by first semester students of Journalism Study Program Bengkulu University academic year 2021-2022. This research was descriptive quantitative. The sample of this research was first semester students of Journalism Study Program Bengkulu University. The data were collected by using a questionnaire. The questionnaire has validated using expert judgments. In this instrument, the reliability obtains by using Cronbach’s Alpha formula in SPSS software. This research used simple statistical (percentage and weighted average) to analyze the data. The results of this research showed that the majority of the students (54 out of 73) were in the medium level of anxiety. There were three factors that cause students’ anxiety in learning English at Journalism Study Program Bengkulu University; Fear of Negative Evaluation, Communication Apprehension, and Test Anxiety. The majority factor that caused students’ Anxiety in learning English at Journalism Study Program Bengkulu University mostly came from fear of negative evaluation.